Activity theory in empirical higher education research: choices, uses and values. Issue 2 (3rd April 2017) - Bligh, Brett; Flood, Michelle
Abstract : This paper contributes to discussion of theory application in higher education research. We examine 59 empirical research papers from specialist journals that use a particular theory: activity theory. We scrutinise stated reasons for choosing the theory, functions played by the theory, and how the theory is valorised. We find that the theory is usually chosen for its direct empirical applicability; used for abstraction, explanation and contextualisation; and valorised for apprehending complex situational dynamics. It is rarely chosen to challenge conceptualisation of the research object; used to establish investigative paradigms; or valorised in ways that implicate wider bodies of knowledge or potential theory development. We argue that higher education researchers should reconsider how their application of activity theory is interwoven with interpretative processes, how the theory might frame research design rather than simply data analysis, and how they account for the range of roles that the theory actually plays across research endeavours.